Anti-PD-L1 blockade facilitates antitumor effects of radiofrequency ablation by improving tumor immune microenvironment in hepatocellular carcinoma - Liang, Jiahua; Ma, Mingjian; Feng, Wei; Xu, Qiongcong; Chen, Dong; Lai, Jiaming; Chen, Jiancong (Apoptosis, 2024)
Hepatocellular carcinoma (HCC) is a complex disease with advanced presentation that significantly affects survival rates. Therefore, novel therapeutic strategies are needed. In this study, we investigate the tumor microenvironment (TME) in HCC by analyzing 13 HCC samples at single cell level. We identified key cell populations, including CD8 + T cells, Tregs, M1/M2 macrophages, and CD4 + memory T cells, and explored their roles and interactions. Our research revealed an early enrichment of CD8 + T cells, which could potentially lead to their exhaustion and facilitate tumor progression. We also investigated the impact of percutaneous radiofrequency ablation (RFA) on the immune microenvironment. Using a dual tumor mouse model, we demonstrated that RFA induces necrosis, enhancing antigen presentation and altering immune responses. Our results indicate that RFA increases PD-L1 expression in residual liver tissue, suggesting potential immune escape mechanisms. Furthermore, the combination of RFA and anti-PD-L1 therapy in the mouse model resulted in significant improvements in immune modulation. This included increased CD8 + T cell efficacy and decreased Treg infiltration. This combination shows promise as an approach to counteract HCC progression by altering the immune landscape. This study highlights the critical interaction within the TME of HCC and suggests the possibility of improving patient outcomes by targeting immune evasion mechanisms through combined therapeutic strategies.
Gesehen am 21.01.2025